Analisis Bahasa dari Kata Hingga Konteks: Kajian Morfologi, Sintaksis, Semantik, dan Pragmatik pada Teks Buku Ajar Bahasa Indonesia Sekolah Dasar Kelas Atas: Penelitian - Oktavia Ramadhani; Kartika Dewi Cahyani; Anglin Dwi Anggraini; Ardiva Salsabila Putri; Arum Sekartaji (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Language is an important foundation in basic education. Upper-level Indonesian language textbooks for elementary schools play a role in developing students' language skills and shaping their character. This study aims to analyze the morphological, syntactic, semantic, and pragmatic aspects of five upper-level Indonesian language textbooks for elementary schools. The study uses a descriptive qualitative approach with a literature review method and content analysis technique. The results of the study indicate that the four linguistic aspects have been applied in an educational manner and in accordance with the cognitive development of students, as well as containing moral and social values. Thus, these texts are considered suitable for use as Indonesian language teaching materials in elementary schools.